HALF DIALLEL ANALYSIS OF SEVEN PEA CULTIVARS FOR SEED YIELD AND ITS COMPONENTS FOR F4 GENERATION UNDER SULAIMANI CONDITION - Hama-Amin, T. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present study was carried out at Qlyasan locations, in Kurdistan Region-Iraq, Agricultural Research Station, College of Agricultural Engineering Sciences-University of Sulaimani, according to half diallel mating system using seven pea cultivars (1-Avolla, 2-Americana, 3-Jeza, 4-Joneor, 5-Pack land, 6-Arvena and 7-Samara) with 21 F4 crosses. The genotypes were planted in a completely randomized block design with three replications. Highly significant mean squares due to genotypes were recorded indicating the presence of sufficient variability among genotypes for all traits. The mean squares due to gca and sca were significant for all the studied traits. The highest positive heterosis values estimated as the F4s deviation from mid parental values recorded by the cross 2×6 and 4×5 for almost all traits. Maximum positive gca effect values for seed weight plant-1, biological yield plant-1 and pods number plant-1 were recorded by parent 4, while parent 2 showed the best value for some components. The cross 4×5 was the best sca combiner for seed weight plant-1 and some its components including pods number plant-1, pod weight plant-1 and seed number pod-1. The type of gene action as controlled the inheritance of all characters was over dominance except 100-seed weight. Heritability in broad sense was found to be high for all treats except seed number pod-1 which was moderate, while at narrow sense it was high for average pod weight, pod length, seed weight pod-1 and 100-seed weight.